Draft Genome Sequence of Pseudomonas oceani DSM 100277(T), a Deep-Sea Bacterium - García-Valdés, Elena (Genome Announc, 2018)
Pseudomonas oceani DSM 100277(T) was isolated from deep seawater in the Okinawa Trough at 1390 m. P. oceani belongs to the Pseudomonas pertucinogena group. Here, we report the draft genome sequence of P. oceani, which has an estimated size of 4.1 Mb and exhibits 3,790 coding sequences, with a G+C content of 59.94 mol%.